ANALYSIS OF COST CONTROL, TIME, AND QUALITY ON CONSTRUCTION PROJECT - Dewi Nusraningrum; Joko Priyono (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2018)
This research aims to analyze the relationship of delay time and costs with estimated that causes increased costs from perspective of management fees project with earned value method and to analyze the influence of the variables associated with the quality control at each stage of the work concreting. Secondary data collection i.e. the draft budget, the curve S, financing and weekly reports the progress of the project. Primary data i.e. questionnaires to 30 respondents. The cost control and time used earned value methods, and quality control with multiple linear regression. The results of the research project performance until the 27th week of aspects of cost and time projects implementation are not experiencing excess costs, but suffered delays. Regression analysis a very influential determinant variables of each job of making concrete to install formwork: concrete level marking and dimensions for formwork, ironing: the connection reinforcement iron and iron a clean free from rust, oil, and dry concrete, for concreting: checking of slump test and the amount of labor, and to uninstall the formwork: concrete age and concrete level according to plan.